JEJAK PRAKTIK MILITERISME DALAM PUISI INDONESIA - Sungkowati, Yulitin (ATAVISME, 2007)
The existence of military in a country does not automatically mean militarism. However, during the New Order era, militarism was used to dominate political life and became a power shield as an excuse to maintain national stability. The military practice could be seen, among other things in Indonesian literary works, particularly in Wiji Thukul's, Rendra's, Eka Budianta's, and K.H. A. Mustafa Bisri's writing as a reflection of his period. These poems depict military action in the New Order power such as in the land reform case, workers protest, and the 27th of July incident. Military action has become a violent pattern to silence these unpleasant incidents. Some critical activists experienced these violent actions such as terror, kidnapping, and torturing,